Morphological Features of Testicular Biopsies in Infertile Males at a Tertiary Hospital, Southwest Nigeria - Adesoji, Adetona; Olufemi, Ogunbiyi (Journal of Fertility Biomarkers, 2021)
Background Male Infertility accounts for 30-40% of all cases of infertility and its evaluation requires a good history, thorough physical examination, and several investigations to include testicular biopsy which might be used to further categorize infertile males for proper management and prognostication. This study aims to determine the predominant histopathological patterns of testicular biopsies in infertile males and to compare the findings with previous studies. Methods A retrospective cross-sectional study of 225 selected cases of testicular biopsies reviewed for the evaluation of male infertility in the Pathology department, of a tertiary hospital, Southwest, Nigeria, between 1987 and 2012. Relevant clinical and histopathological information was extracted from the departmental records. All histologic cases were reviewed, and a classification based on histological patterns of spermatogenesis was utilized to group the cases into normal findings, hypo spermatogenesis, maturation arrest, Sertoli cell-only syndrome, peritubular hyalinization/ tubular fibrosis and mixed patterns. The data obtained were analysed using descriptive and inferential statistics at a 5% level of significance. Results Among the 225 cases reviewed with a mean age of 37.7 years (SD - 8.61), 82.7% had primary infertility of which 92.9% were azoospermic, while 7.1% had oligospermia. The histological patterns included 34.2% of Hypospermatogenesis, 32% of Peritubular hyalinization/ tubular fibrosis, 14.2% had maturation arrest and Sertoli cell-only syndrome was found in 6.7% of cases, only 0.9% had normal histologic pattern while the mixed histologic pattern was seen in 12% of cases. Conclusion The commonest morphological pattern was Hypospermatogenesis, which is similar to some of the previous local and international studies. A high percentage of peritubular fibrosis was noted with few tubules containing scanty late spermatids or spermatozoa when proper sampling and evaluation were made. Multiple patterns within a biopsy were seen with careful review, especially in non-obstructive azoospermic cases. This is significant in male infertility patient management in our environment because it suggests greater chances of successful sperm extraction for Assisted Reproduction Technique in such patients.
Keywords: Male infertility; biopsy; Testis